2017
DOI: 10.1590/s1806-92902017000100001
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance of female Nile tilapia ( Oreochromis niloticus ) fed diets with different digestible energy levels

Abstract: This study aimed to evaluate the reproductive performance of female Nile tilapia (Oreochromis niloticus) fed diets containing different levels of digestible energy (DE). The fish were housed in 15 fiberglass tanks (500 L) in a recirculating system at an average temperature of 27.5 °C. The treatments consisted of five diets with increasing levels of DE (3,200; 3,400; 3,600; 3,800; and 4,000 kcal/kg). The levels of DE did not significantly influence the final weight or the hepatosomatic, gonadosomatic, and visce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
(29 reference statements)
0
5
0
1
Order By: Relevance
“…Additionally, other studies have indicated that biofloc consumed by fish improves digestion and decreases the feed conversion ratio (Avnimelech 2009). In our study, an FCR greater than 2 was expected due to the interaction between sexes, since the tilapia culture was of mixed sexes, energy from food may have been partially used to satisfy reproductive needs, such as gonad maturation or territorial defense (Orlando et al 2017).…”
Section: Discussionmentioning
confidence: 66%
“…Additionally, other studies have indicated that biofloc consumed by fish improves digestion and decreases the feed conversion ratio (Avnimelech 2009). In our study, an FCR greater than 2 was expected due to the interaction between sexes, since the tilapia culture was of mixed sexes, energy from food may have been partially used to satisfy reproductive needs, such as gonad maturation or territorial defense (Orlando et al 2017).…”
Section: Discussionmentioning
confidence: 66%
“…This energy allocation process in fish can be influenced by the tropic category, food quality, habitat conditions and specific reproductive strategy (dos Santos et al, 2010;Espínola et al, 2014). Therefore, knowledge of energy metabolism in fish is an indispensable tool for the preparation of suitable artificial diets during the prespawning period (Orlando et al, 2017). Tilapia, the most important aquaculture species of the 21st century, accounts for 10% of the world's finfish production (FAO, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of studies on fish bioenergetics in freshwater fishes in their natural environment (Carolina & Doria Izabel de Fatima, 1997), hitherto, very few papers have been published on Nile tilapia (Lupatsch et al ., 2010; Orlando et al ., 2017), but there is no available information on O. mossambicus . Further, studies that quantify the pattern of energy‐level changes in the ovary during development have not been attempted.…”
Section: Introductionmentioning
confidence: 99%
“…Nile tilapia is a mouthbrooder species, and the females protect the eggs by incubating them in their mouth until hatching ( Konstantinidis et al, 2020 ). This form of parental care increases offspring survival and fitness; the epidermal mucus of female tilapia changes to ensure protection, development and capacity enhancement of the embryos/fry under different situations, for example, during transport to new locations/environments ( Iq and Shu-Chien, 2011 ; Orlando et al, 2017 ). Buccal cavity mucus of female tilapia has an array of proteins, namely antioxidant enzymes such as peroxiredoxin and stress proteins like heat shock proteins that are upregulated during infection and parental care ( Iq and Shu-Chien, 2011 ).…”
Section: Introductionmentioning
confidence: 99%